Ópera saindo da caixa : atravessamentos decoloniais em óperas brasileiras contemporâneas - Dickmann, Maidi Leonice (2023)
This thesis discusses the tensions between decolonial and hegemonic elements in contemporary Brazilian operas. To this end, studies were carried out on the constitution of colonial and decolonial thought, the relations of power, being and knowledge in foreign and Brazilian opera, the conceptions of the term opera in works circulating in Brazil were brought and discussed, and I also explain my conception of opera. Afterwards, three contemporary Brazilian operas accessible via digital media were analyzed, which are: As Malibrans (2000), by Jocy de Oliveira, Lídia de Oxum (2019), by Lindembergue Cardoso and Ildásio Tavares, and Ópera Café (2022), by Felipe Senna and Sérgio de Carvalho. The operas studied have the last three decades as a time frame and address decolonial themes of gender, ethnic-racial relations and subalternity. The analyses were undertaken as an exploratory investigation of the data, in which the variables and the relationships between them are discussed regarding the theme and artistic elements in instrumental music, vocal music, in theatricality, in body expressions and/or dance and in visuals. The data revealed that in Brazil there are operatic performances in which these themes and artistic elements were reworked, bringing other perspectives to the Brazilian operatic context.